(untitled) (Heritage, 2022)
The paper points out, first of all, the fact that the contemporary migrant crisis represents a projected emigration of people and that everything that is happening in the world today (the so-called Arab Spring - a wave of demonstrations, protests and rebellions, started in December 2010 in Tunisia and continued in other countries of North Africa and the Middle East, wars in certain countries, millions of homeless people, refugees and migrants, etc.) is not accidental at all. International law and its theoretical principles have never been more developed, on the one hand, but they have never been violated or compromised in practice, applied by naked political force and political power, on the other hand. Namely, all this is an integral part of the realization of the idea of the New World Order, which is by no means new. The destruction of "national sovereignty" and the creation of "limited sovereignty", the de-sovereignation of national states is the harsh reality of the modern world. This is done through the creation of supranational regional organizations (for example, the European Union) and institutions of global financial power (the World Bank, the International Monetary Fund, the World Trade Organization, and others).